PEMANFAATAN LIMBAH MINYAK GORENG SEBAGAI BAHAN SABUN KRIM CUCI PIRING ARANG AKTIF: Utilization of Waste Cooking Oil as Activated Charcoal Dishwashing Cream Soap - Emil Wahdi (IPB University, 2023)
Waste cooking oil (jelantah) is frying waste from palm oil that has been used repeatedly and continuously.This type of waste cannot be disposed of directly into the environment because it can contaminate the surrounding area. Waste cooking oil can be used as a raw material for activated charcoal dishwashing cream soap. Activated charcoal solid soap is prepared by adding waste cooking oil to 137 gr NaOH, 500 ml water, 2.5 gr NaCl, 1 gr 4Na-EDTA, and 40 gr finely activated charcoal. Diced solid soap is then dissolved in ethanol 70% and glycerin to form a paste (cream). The results of this study indicate that the chemical characteristics of cream soap from used cooking oil are not different from those made from new palm cooking oil. The water content of activated charcoal cream soap from used cooking oil is 40.60% and pH 10.6 and the water content of new palm cooking oil is 40.32% and pH 10.6. It was concluded that waste cooking oil can be used as an ingredient in activated charcoal dishwashing cream and provides more economic and environmental benefits. ABSTRAK Minyak goreng bekas (jelantah) merupakan limbah penggorengan dari minyak sawit yang telah digunakan secara berulang dan terus menerus. Jenis limbah ini tidak bisa langsung dibuang ke lingkungan karena dapat mencemari daerah sekitarnya. Minyak jelantah dapat dimanfaatkan sebagai bahan baku sabun krim cuci piring arang aktif. Sabun padat arang aktif dibuat dengan cara penambahan minyak jelantah dengan 137 gr NaOH, 500 ml air, 2.5 gr NaCl, 1 gr 4Na-EDTA, dan 40 gr arang aktif halus. Sabun padat dipotong dadu kemudian dilarutkan dengan etanol 70% dan gliserin menjadi pasta (krim). Hasil penelitian ini menunjukkan bahwa karakteristik kimia dari sabun krim dari minyak jelantah tidak berbeda dengan sabun yang berasal dari minyak goreng sawit baru. Kadar air sabun krim arang aktif dari minyak jelantah yaitu 40.60% dan pH 10.6 serta kadar air dari minyak goreng sawit baru 40.32% dan pH 10.6. Disimpulkan bahwa minyak jelantah dapat digunakan sebagai bahan krim cuci piring arang aktif dan memberi manfaat lebih terhadap ekonomi dan lingkungan.